Psychology on the ‘ground’ of the school: : an analysis of practices in confronting violence (Brazilian Journal of Health Research, 2025)
Introduction: This study explores the role of Psychology in schools in addressing violence, highlighting both the challenges and the potential of such practices. It adopts a theoretical and reflective approach, analyzing the relationship between Psychology and the School, and emphasizing the need for institutional practices that go beyond individualizing responses to violence. The study also discusses the importance of interdisciplinary work and integrated public policies. Objectives: To examine the relationship between Psychology and the School in the context of violence, and to reflect on how to sustain a critical practice that balances the urgency of interventions with the need to transform institutional structures that perpetuate violence. Methods: This is a qualitative study grounded in institutional analysis, literature review, and the examination of normative and academic documents. Results: Viewing the school as a space of tension and dispute, the process of transformation occurs through relationships between psychologists and the school community, between students and educational staff, and between schools and families. Addressing violence is built through collaboration among various actors and through the critical examination of established practices. Conclusion: Addressing school violence requires a collective and interdisciplinary effort aimed at transforming the institutional and social conditions that sustain the reproduction of violence.
Keywords: Violence; Education; Institutional analysis